Pregnancy rate in dairy cows treated with human chorionic gonadotropin five days after insemination - Urzúa González, Ernesto; Valdés Pérez, Luis Ángel; Garza, Agustín; Mapes, Gabriela; Gutiérrez, Carlos G; Hernández-Cerón, Joel (Austral Journal of Veterinary Sciences, 2017)
This study tested whether the administration of hCG five days after insemination increased progesterone concentration and pregnancy rate (PR) in dairy cows. A total of 989 lactating Holstein cows with different parity and number of prior services were used. Cows were inseminated after overt estrus or at a fixed-time. Five days post-insemination, cows were randomly assigned to two treatment groups: hCG (n=482), which received 3500 IU of hCG by intramuscular injection; and the control group (n=507), which did not receive any treatment. Pregnancy was diagnosed by ultrasound on day 30 post-insemination, and gestation was confirmed on day 60 post-insemination by rectal palpation. In 15 cows from each treatment group, plasma progesterone concentration was determined on days 5, 11, and 15 post-insemination. Pregnancy rate was analysed using logistic regression. Variations in progesterone concentration between treatments were tested by ANOVA for repeated measurements. Progesterone concentration was higher on days 11 and 15 in cows treated with hCG, compared to the control group (P<0.05). Treatment with hCG increased pregnancy rate (47.5 vs. 37.4%. Odds ratio 1.3; P<0.05). No interaction was observed between treatment and body condition, prior services, milk production, parity, or insemination type (overt estrus or fixed time). Treatment with hCG did not reduce pregnancy losses between day 30 and 60 post-insemination (P>0.1). We conclude that injection of hCG five days after insemination increased progesterone concentration and pregnancy rate in dairy cows.